2010
DOI: 10.1186/1471-2458-10-147
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cross-sectional associations between common childhood illness, housing and social conditions in remote Australian Aboriginal communities

Abstract: BackgroundThere is limited epidemiological research that provides insight into the complex web of causative and moderating factors that links housing conditions to a variety of poor health outcomes. This study explores the relationship between housing conditions (with a primary focus on the functional state of infrastructure) and common childhood illness in remote Australian Aboriginal communities for the purpose of informing development of housing interventions to improve child health.MethodsHierarchical mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 29 publications
6
86
3
Order By: Relevance
“…This study's findings regarding the association between middle ear disease and previous episodes of ear infection and increasing household number are consistent with large international cohort studies (Labout et al 2011), one of which also identified low socioeconomic status as a risk factor (Paradise et al 1997). However, our findings differ from the two other epidemiological studies involving Aboriginal populations in rural and remote areas (Jacoby et al 2008;Bailie et al 2010) and a meta-analysis examining risk factors for middle ear disease (Uhari et al 1996), which found that environmental tobacco smoke and childcare attendance were important risk factors. In the Kalgoorlie cohort study, overcrowding, defined as more than one person per room, was not significantly associated with specialistdiagnosed otitis media.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This study's findings regarding the association between middle ear disease and previous episodes of ear infection and increasing household number are consistent with large international cohort studies (Labout et al 2011), one of which also identified low socioeconomic status as a risk factor (Paradise et al 1997). However, our findings differ from the two other epidemiological studies involving Aboriginal populations in rural and remote areas (Jacoby et al 2008;Bailie et al 2010) and a meta-analysis examining risk factors for middle ear disease (Uhari et al 1996), which found that environmental tobacco smoke and childcare attendance were important risk factors. In the Kalgoorlie cohort study, overcrowding, defined as more than one person per room, was not significantly associated with specialistdiagnosed otitis media.…”
Section: Discussioncontrasting
confidence: 54%
“…Middle ear disease was less prevalent in this urban context than in previous studies in rural/remote Aboriginal communities (Morris et al 2005;Bailie et al 2010).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…However, other risk factors can, to some extent, be influenced. One such example is day care, which has been associated with an increased risk of AOM [29,30]. Multiple studies provide evidence that breastfeeding for at least 4-6 months reduces the number of AOM episodes and the risk of recurrent AOM [31,32].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…109 However, there are other household determinants such as the quality of household infrastructure and amenities that contribute to health outcomes for Aboriginal peoples. 394 Participants' perception of household crowding as an issue in their house may be the most valid measure of household crowding as it is associated with participants' sense of how habitable their house is. 393 The HA contains a question as part of the NLES asking participants if overcrowding is an issue for them.…”
Section: Physical Environmentmentioning
confidence: 99%